Application of list management mode in nosocomial infection prevention in the prosthodontics clinic (口腔修复门诊实施院内感染清单式管理的效果分析) - WANG Meng (王蒙); LIU Xuewei (刘学伟); GAN Ling (甘泠); YAN Tong (晏桐); CUI Yue (崔悦); CAI Shuang (蔡爽); WANG Wei (王威) (中西医结合护理)
Objective To analyze the list management mode in nosocomial infection prevention in the prosthodontics clinic. Methods Based on the analysis of problems found in nosocomial infection monitoring, a checklist management was implemented in prevention of nosocomial infection in the dental prosthesis clinic from August 2021 to December 2022, including air quality in the consulting room, medical devices, dental impressions, and hand hygiene of medical staff. After three times of airborne bacterial culture in the consulting room, sampling and bacteriological testing of the surfaces of instruments, dental impressions, and hands of medical staff, the monitoring results were recorded in detail. The quality monitoring data of nosocomial infection control in were compared before and after implementation, and the implementation effect was analyzed. Results The bacterial colony count of air in the consulting room was decreased after implementation of list management(P＜0. 01). The bacterial colony count of instrument surface, impression surface and hands of medical staff after implementation of list management were lower than those before implementation of list management (P＜0. 01). The qualified rates of colony monitoring on the air, hands of medical staff and the surface of the medical sterilizing tray were significantly higher than those before implementation of list management(P＜0. 01). The incidence of nosocomial infection after implementation of list management was significantly lower than that before implementation of list management (P＜0. 01). Conclusion The implementation of nosocomial infection list management can effectively reduce the bacteriological detection rate of air dust, instrument surface, impression surface and medical staff's hand, and reduce the risk of nosocomial infection, which is worthy of clinical promotion. (目的 分析口腔修复门诊实施院内感染清单式管理的效果。方法 针对院内感染监测发现的问题, 于2021年8月—2022年12月在医院口腔修复门诊实施包括诊室空气质量、医疗器械、口腔印模、医护人员手卫生的清单式管理。经过3次诊室空气培养, 器械表面、印模表面及医护人员手部采样和细菌学检测, 详细记录监测结果, 对比实施前后口腔修复门诊院内感染控制质量监测数据的差异, 分析实施效果。结果 清单式管理实施后, 口腔科门诊空气菌落计数较清单式管理实施前下降(P＜0. 01); 医护人员手部、口腔印模表面、医疗器械表面菌落计数较清单式管理实施前下降(P＜0. 01); 口腔科门诊空气、医护人员手部、托盘消毒储存监测合格率较清单式管理实施前提升(P＜0. 01); 患者院内感染发生率较实施前下降(P＜0. 01)。结论 口腔修复门诊实施院内感染清单式管理可有效减少诊室空气粉尘、器械表面、印模表面、医护人员手部的细菌学检出率, 降低院内感染风险。)